A Constrained Helical Peptide Against S100A4 Inhibits Cell Motility in Tumor Cells. (15th April 2015) - Naiya, Gitashri; Kaypee, Stephanie; Kundu, Tapas K.; Roy, Siddhartha
<x xml:space="preserve">Abstract</x> S100A4, a member of a calcium‐regulated protein family, is involved in various cellular signaling pathways. From many studies over the last decade or so, it has become clear that it is involved in tumor metastasis, probably playing a determinative role. However, except the phenothiazine group of drugs, no significant inhibitor of S100A4 has been reported. Even the phenothiazines are very weak inhibitors of S100A4 action. In this study, we report design and development of a conformationally constrained helical peptide modeled on the non‐muscle myosin peptide that binds to S100A4. This conformationally constrained peptide binds to S100A4 with a dissociation constant in the nanomolar range. We also synthesized a peptide for experimental control that bears several alanine mutations in the peptide–protein interface. We demonstrate that the former peptide specifically inhibits motility of H1299 and MCF‐7 cells in a wound‐healing assay. Structures of several S100A4–ligand complexes suggest that it may be possible to develop a smaller peptide–small molecule conjugate having high affinity for S100A4. Peptide–drug conjugates of this kind may play an important role in developing drug leads against this antimetastasis target.